Development and evaluation of a multimedia interactive CD: Public speaking interactive media - Abdul Rahim, Azwin Arif (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
This paper reports on a study that endeavours to develop a Computer Assisted Learning (CAL) multimedia courseware namely, Public Speaking Interactive Media. This courseware was developed specifically for diploma students undergoing ENG4113 (Business English) and ENG 4153 (Public Speaking Skills) at Kolej Profesional MARA Indera Mahkota, Kuantan, Pahang. The objectives and goals of this study is to develop a CAL courseware which is in-line with the syllabus of the courses using multimedia elements together with the application of behaviorist, cognitive and constructivist learning theories as a basis in the design of the courseware. Moreover, the instructional design and implementation of this CAL multimedia courseware employ active and flexible learning strategies. Utilizing Hannafin and Peck’s Design Model, this courseware was developed using Macromedia Director and Macromedia Authorware to ensure that multimedia elements and simulations can be fully integrated. The findings of the study revealed that the courseware fulfilled its objectives in aiding students in comprehending the concept of public speaking skills better by using multimedia elements. In addition, the courseware is in-line with the syllabus and has incorporated the theories and strategies intended successfully.